2018
DOI: 10.1002/jcb.27671
|View full text |Cite
|
Sign up to set email alerts
|

MAPKs and NF‐κB‐mediated acrylamide‐induced neuropathy in rat striatum and human neuroblastoma cells SY5Y

Abstract: Acrylamide (ACR) is a potent neurotoxin that can be produced during hightemperature food processing, but the underlying toxicological mechanism remains unclear. In this study, the detrimental effects of ACR on the striatal dopaminergic neurons and the roles of mitogen-activated protein kinases (MAPKs) and nuclear factor κB (NF-κB) in ACR-induced neuronal apoptosis were investigated. Acute ACR exposure caused dopaminergic neurons loss and apoptosis as revealed by decreased tyrosine hydroxylase (TH)-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…As seen in previous studies, acrylamide exposure induces an inflammatory response by the release of various cytokines. [6][7][8]17,27,33 In the present study, the TNF-α and IL-1β levels were found high in rat brains exposed to acrylamide. The same cytokines were found to be high in the acrylamide-treated rat brains in a study by Goudarzi et al 9 This suggests that inflammation may play a role in the development of acrylamide-induced brain damage.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…As seen in previous studies, acrylamide exposure induces an inflammatory response by the release of various cytokines. [6][7][8]17,27,33 In the present study, the TNF-α and IL-1β levels were found high in rat brains exposed to acrylamide. The same cytokines were found to be high in the acrylamide-treated rat brains in a study by Goudarzi et al 9 This suggests that inflammation may play a role in the development of acrylamide-induced brain damage.…”
Section: Discussionsupporting
confidence: 55%
“…neuron loss. 17 In the in vitro study of Park et al a high dose of 50 mg/kg was shown to trigger the death of neural progenitor cells and to impair adult hippocampal neurogenesis by increased intracellular ROS levels. 18 Acrylamide directly targets nerve terminals causing synaptic dysfunction via neurotransmitter release impairment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations